Persistence of surrogates for high consequence viral and bacterial pathogens in a pilot-scale activated sludge treatment system - Schupp, Donald A.; Burdsall, Adam C.; Silva, Rendahandi G.; Heckman, John Lee; Krishnan, E. Radha; Szabo, Jeffrey G.; Magnuson, Matthew (PloS one, 2022)
The persistence of high consequence public health pathogens in a wastewater treatment system can significantly impact worker safety, as well as the public and downstream water bodies, particularly if the system is forced to shut down the treatment processes. This study utilizes organism viability to compare the persistence of three pathogen surrogates in wastewater using a pilot-scale activated sludge treatment (AST) system, operated to mimic treatment processes of large-scale plants. Bacillus globigii spores, surrogate for Bacillus anthracis , persisted in the AST system for at least a 50-day observation period leading to a possible steady condition far beyond the solid retention time for sludge particles. MS2 bacteriophage, surrogate for Poliovirus and other non-enveloped enteric viruses, was observed for up to 35 days after introduction, which largely and expectedly correlated to the measured solid retention time. Phi-6 bacteriophage, a surrogate for Ebola virus and other enveloped viruses, was detected for no more than 4 days after introduction, even though the AST system was operated to provide three times slower solids removal than for the other surrogates. This suggests Phi-6 is subject to inactivation under AST conditions rather than physical removal. These results may suggest similar persistence for the surrogated pathogens, leading to appropriate consequence management actions.